249 Stroke network, stroke, intravenous thrombolysis, intra-hospital delay, imaging. (23rd September 2015) - Girot, M; Wiel, E; Hardy, A; Smith, G; Pruvo, J P; Leclerc, X; Goldstein, P
Abstract : Aim and Background: The stroke network is organised around the Stroke Unit (SU) which is known to be effective to reduce mortality and handicap in all types of strokes. However, most of patients do not receive imaging in a timely manner, only 40% of patients admitted in a hospital with SU are hospitalised in this unit and less than 1% of patients are thrombolysed. The aim of our study was to evaluate the efficacy of the stroke network before the stroke unit for improving. Programme: We conducted a prospective study during 2 months to evaluate the intra-hospital management of patients admitted for suspected stroke in emergency department (ED) before the SUof our University Hospital in terms of delay, imaging and orientation. We compared the length of stay in ED for patients admitted for suspected stroke and for patients hospitalised for other neurological reasons. Results: 258 patients were admitted for suspected stroke. This diagnosis was confirmed in 225 patients, including 44 transient ischaemic attack, 155 ischaemic stroke, 26 hemorrhagic stroke; 13 patients received intravenous thrombolysis. 27% were admitted within 3 h after symptom onset, 8% between 3 and 4 h 30 and 20% awaked with stroke. The delay of admission was significantly shorter in patients with hemorrhagic stroke and in patients for whom the emergency telephone system have been used. Median delay for imaging was1 h 59 min in the all population and was 53 min for patients admitted within 3 h. Only 12% of patients received CT scan within 25 min of hospital admission. Two third of the patients were admitted in stroke unit. The mean length of stay at the ED was 25 min for thrombolysis patients, 5 h 20 for the others admitted in stroke unit and 5 h 57 for all the population hospitalised for stroke, which did not differ from the length of stay for the other neurological hospitalisations. Discussion: The impact of the stroke network is proved by the high percentage of patients admitted in stroke unit and the shorter delay of management for patients who are thrombolysed. However, the benefit is not observed for all patients with stroke. Conclusion: These data suggest areas for improvement in hospital-level stroke system of care which could increase patient access to stroke unit and therefore potentially reduce stroke related morbidity and mortality. It should be recommended for all patients admitted for stroke and not only for patients who can be thrombolysed. Objectif(s), Contexte: Les autorités sanitaires françaises ont favorisé la mise en place d'une filière d'organisation des soins, structurée autour de l'unité neurovasculaire (UNV) dont le bénéfice est attendu quel que soit l'âge du patient, le type et la sévérité de l'AVC. Malgré cette organisation, l'accès rapide à l'imagerie est réservé à une minorité de patients, 40% des patients admis dans un établissement avec UNV y sont admis et moins de 1% des patients victimes d'AVC sont actuellement thrombolysés. L'objectif de notre travail est d'analyser le fonctionnement de la filière neurovasculaire (fNV) en amont de l'UNV afin de l'optimiser. Programme: Nous avons mené une étude prospective sur une période de 2 mois en analysant les modalités de prise en charge intra-hospistalière (délais d'admission, accès à l'imagerie, durée de séjour, orientation) des patients admis pour AVC dans le SAU du CHU de Lille en amont de l'UNV. Nous avons comparé, dans un deuxième temps, le délai de séjour des patients admis pour AVC à celui des patients hospitalisés pour un autre motif neurologique. Résultats: 250 patients suspects d'AVC ont été admis, ce diagnostic a été retenu chez 225 d'entre eux. Il s'agissait de 44 accidents transitoires et 181 accidents constitués dont 155 d'origine ischémique ; parmi eux 13 ont été thrombolysés. 27% des patients étaient admis dans les 3h ; 8% entre 3-4h30 et 20% avaient un AVC du réveil. Les délais d'admission sont plus courts chez les patients ayant bénéficié d'une régulation et chez ceux dont l'accident est de nature hémorragique. Tous les patients ont eu un scanner cérébral dont le délai médian de réalisation était de 1h59. Pour les patients admis dans les 3 heures le délai médian était de 53 minutes. Au total, seuls 12% des patients ont eu leur imagerie dans les 25 minutes après leur admission conformément aux recommandations. Au terme de la prise en charge, 2 patients sur 3 ont été admis en UNV. Le durée de séjour au SAU pour les patients admis en UNV était de 5h20 après exclusion des patients thrombolysés (pour qui le délai était de 25 minutes), ce délai était de 5h57 pour l'ensemble des admissions pour AVC, il ne différait pas significativement des autres motifs d'admission en neurologie. Discussion: Il existe un effet filière avec plus de 60% des patients admis en UNV et des délais plus courts pour les patients éligibles pour une thrombolyse. Cependant, ce bénéfice en termes de délai ne se répercute pas sur l'AVC « standard » dont les délais de prise en charge et de durée de séjour restent prolongés au SAU alors que les premières heures de l'AVC sont décisives tant sur le plan physiopathologique que thérapeutique. Conclusion: Le développement d'une prise en charge structurée des AVC doit maintenant s'étendre à tous les AVC et non pas aux seuls patients susceptibles de bénéficier d'une thrombolyse.